2022
DOI: 10.3389/fnhum.2022.943469
|View full text |Cite
|
Sign up to set email alerts
|

Motor Cortex Response to Pleasant Odor Perception and Imagery: The Differential Role of Personality Dimensions and Imagery Ability

Abstract: BackgroundNeuroimaging studies have shown a complex pattern of brain activation during perception of a pleasant odor and during its olfactory imagery. To date, little is known regarding changes in motor cortex excitability during these tasks. Bergamot essential oil (BEO) is extensively used in perfumes and cosmetics for its pleasantness. Therefore, to further our understanding of the human sense of smell, this study aimed to investigate the effect of perception and imagery of a pleasant odor (BEO) on motor cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 67 publications
0
2
0
Order By: Relevance
“…Fourteen of the reviewed papers weighed in on the debate regarding olfactory memory processes. Whilst only three of the reviewed papers actively studied olfactory memory ( Plailly et al, 2007 ; Meunier et al, 2014 ; Eek et al, 2023 ), eleven papers were able to apply their findings to contribute further knowledge to the discussion of olfactory memory ( Djordjevic et al, 2004 ; Bensafi and Rouby, 2007 ; Plailly et al, 2011 ; Hudry et al, 2014 ; Kollndorfer et al, 2015a ; Zhou et al, 2019 ; Callara et al, 2021 ; Infortuna et al, 2022 ; Torske et al, 2022 ; Muccioli et al, 2023 ; Perszyk et al, 2023 ). Memory of odours and olfactory experiences presents a unique case of memory encoding and recall compared to other sensory modalities ( Stevenson and Case, 2005 ; White, 2009 ; Eek et al, 2023 ).…”
Section: Methodsmentioning
confidence: 99%
“…Fourteen of the reviewed papers weighed in on the debate regarding olfactory memory processes. Whilst only three of the reviewed papers actively studied olfactory memory ( Plailly et al, 2007 ; Meunier et al, 2014 ; Eek et al, 2023 ), eleven papers were able to apply their findings to contribute further knowledge to the discussion of olfactory memory ( Djordjevic et al, 2004 ; Bensafi and Rouby, 2007 ; Plailly et al, 2011 ; Hudry et al, 2014 ; Kollndorfer et al, 2015a ; Zhou et al, 2019 ; Callara et al, 2021 ; Infortuna et al, 2022 ; Torske et al, 2022 ; Muccioli et al, 2023 ; Perszyk et al, 2023 ). Memory of odours and olfactory experiences presents a unique case of memory encoding and recall compared to other sensory modalities ( Stevenson and Case, 2005 ; White, 2009 ; Eek et al, 2023 ).…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, sensory processing, including olfactory, has been shown to influence motor processing (Ebner, 2005 ). In a recent study using transcranial magnetic stimulation, the perception of a pleasant smell and its olfactory imagery showed to be associated with primary motor cortex excitability (Infortuna et al, 2022 ). The results were in line with those of Rossi et al ( 2008 ), which showed a cross-link between the olfactory and motor systems.…”
Section: Introductionmentioning
confidence: 99%